PENGARUH MOTIVASI DAN STRES KERJA PADA KINERJA PEGAWAI DI PT. CITRA NIAGA LOGISTIK SURABAYA - Quincy Alifany Ku; Is Fadhillah (LP2M Universitas Bina Bangsa, 2023)
This study aims to determine the influence of motivation and work stress on employee performance at PT Citra niaga logistics. in the era of globalization now many companies are demanding employees to do more without paying attention to the level of work stress on employees which results in reduced employee performance and it also has an impact on the company. Therefore, motivation and work stress are very influential on employee performance and can have an impact on the company. This study uses HRM theories related to performance, work motivation, and work stress the approach used in this study is an associative approach. This research will be conducted at PT Citra Niaga logistics Surabaya by distributing questionnaires to employees of PT Citra Niaga logistics. this study used 60 respondents and the method in this study was quantitative. The conclusions and results obtained in this study are motivation and work stress have a significant effect on employee performance at PT Citra Niaga Logistics Surabaya